2018
DOI: 10.1039/c8nj04470h
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of sandwich and multidecker complexes via π⋯π interaction: a DFT study

Abstract: Sandwich and multidecker complexes via organic π–inorganic π interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…For example, ΔE av values for O 2 ‐B 2 H 6 ‐O 2 , C 2 H 4 ‐B 2 H 6 ‐C 2 H 4 , and C 2 H 2 ‐B 2 H 6 ‐C 2 H 2 sandwiches are 0.45, 1.0, and 0.95 kcal mol −1 , respectively while for B 2 H 6 ‐O 2 , B 2 H 6 ‐C 2 H 4 , and B 2 H 6 ‐C 2 H 2 half sandwiches the estimated ΔE values are 0.4, 0.9, and 0.9 kcal mol −1 , respectively. Literatures on sandwiches involving B‐H b ⋯π and π⋯π interactions (arene) have predicted lower ΔE av as compared to their corresponding ΔE values for half sandwiches . The strength of B‐H b ⋯π interaction with localized π‐systems are significantly smaller than that with delocalized π‐systems.…”
Section: Stabilization Energies Of the Complexesmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, ΔE av values for O 2 ‐B 2 H 6 ‐O 2 , C 2 H 4 ‐B 2 H 6 ‐C 2 H 4 , and C 2 H 2 ‐B 2 H 6 ‐C 2 H 2 sandwiches are 0.45, 1.0, and 0.95 kcal mol −1 , respectively while for B 2 H 6 ‐O 2 , B 2 H 6 ‐C 2 H 4 , and B 2 H 6 ‐C 2 H 2 half sandwiches the estimated ΔE values are 0.4, 0.9, and 0.9 kcal mol −1 , respectively. Literatures on sandwiches involving B‐H b ⋯π and π⋯π interactions (arene) have predicted lower ΔE av as compared to their corresponding ΔE values for half sandwiches . The strength of B‐H b ⋯π interaction with localized π‐systems are significantly smaller than that with delocalized π‐systems.…”
Section: Stabilization Energies Of the Complexesmentioning
confidence: 93%
“…It has already been reported that ΔE values for sandwiches are higher as compared to half sandwiches formed via B‐H b ⋯π and π⋯π interactions . Stability of the sandwiches can be better expressed from the average stabilization energy (ΔE av ) that is defined as the total stabilization energy divided by total number of B‐H b ⋯π interactions in the complex.…”
Section: Stabilization Energies Of the Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although B3LYP‐D3(BJ)/cc‐pVTZ level of theory produced relatively accurate results for the model systems, considering the size of the complexes instead of re‐optimization, single point calculations are performed on the optimized geometries at B3LYP‐D3(BJ)/cc‐pVTZ level of theory. Recent literatures also validated the suitability of this protocol for scrutinizing the role of basis sets . Apart from this, to check the consistency of the results, geometries are re‐optimized at M06‐2X/6‐31++G(d,p) and ωB97X‐D/6‐31++G(d,p) level of theories.…”
Section: Resultsmentioning
confidence: 96%
“…Recent literatures also validated the suitability of this protocol for scrutinizing the role of basis sets. [26] Apart from this, to check the consistency of the results, geometries are re-optimized at M06-2X/6-31 + + G(d,p) and ωB97X-D/6-31 + + G(d,p) level of theories. This would enable to gauze the role of functional in predicting the stability of the complexes.…”
Section: Stabilization Energies Of the Complexesmentioning
confidence: 99%